Penggunaan Acidifier sebagai Feed Additive dalam Pakan yang Mengandung Probiotik terhadap Bobot dan Prosentase Bursa Fabrisius dan Limpha Ayam Broiler - Muhammad Koko Mahardi; Bambang Hartoyo; Mohandas Indradji (Fakultas Peternakan Universitas Jenderal Soedirman, 2020)
Background. The Use of Acidifiers as Feed Additives in Feeds Containing Probiotics for Weight and Percentage of Fabricius and Limpha Exchanges Broiler Chicken, Research was conducted on 1-30 September 2019 at the Experimental Farm of the Faculty of Animal Husbandry, Jenderal Soedirman University, Purwokerto, Banyumas Regency. The research aims to examine the use of Acidifier as Feed Additive in Feeds that Contain Probiotics for Weight and Percentage of Fabrisius and Limpha Exchange Broilers. Materials and methods. The study was conducted using an experimental method with a completely randomized design with 4 treatments and 5 replications namely fabrisius exchange R0 = Basal Ration (BS) : 0,88 ± 1,49 %, R1 = BS + Citric acid Acidifier : 0,95 ± 1,15 %, R2 = BS + lactic acid Acidifier : 0.82 ± 1,10 %, R3 = BS + formic acid Acidifier : 0,91 ± 1,55%. Limpha R0 = Basal Ration (BS) : 0,09 ± 1,53 % R1 = BS + Citric acid Acidifier : 0,07 ± 0,13% R2 = BS + lactic acid Acidifier : 0,12 ± 0,16 %, R3 = BS + formic acid Acidifier = 0,10 ± 0,17%. Results. The results showed that the Acidifier did not have a real effect on increasing the increase or development of the Weight, Percentage of Fabricius and Limpha Exchanges